1998
DOI: 10.1074/jbc.273.5.2835
|View full text |Cite
|
Sign up to set email alerts
|

The Solution Structure and Dynamics of the Pleckstrin Homology Domain of G Protein-coupled Receptor Kinase 2 (β-Adrenergic Receptor Kinase 1)

Abstract: The solution structure of an extended pleckstrin homology (PH) domain from the beta-adrenergic receptor kinase is obtained by high resolution NMR. The structure establishes that the beta-adrenergic receptor kinase extended PH domain has the same fold and topology as other PH domains, and there are several unique features, most notably an extended C-terminal alpha-helix that behaves as a molten helix, and a surface charge polarity that is extensively modified by positive residues in the extended alpha-helix and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 56 publications
0
69
0
Order By: Relevance
“…This region exhibits similarity to the basic residues in the extended PH domain of GRK2, i.e. the molten helix, involved in interaction with G␤␥ (28,29). Other studies have illustrated the importance of sequence in the Y-domain of PLC-␤2 in G␤␥-promoted activation (39), and therefore the precise structural determinants for activation of PLC-␤ isozymes by G␤␥ remain to be resolved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This region exhibits similarity to the basic residues in the extended PH domain of GRK2, i.e. the molten helix, involved in interaction with G␤␥ (28,29). Other studies have illustrated the importance of sequence in the Y-domain of PLC-␤2 in G␤␥-promoted activation (39), and therefore the precise structural determinants for activation of PLC-␤ isozymes by G␤␥ remain to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…This ␣-helical extension is rich in arginine and lysine residues and thus reminiscent of the highly mobile, positively charged "molten helix" observed in the NMR structure of the human GRK2 PH domain (PDB code 1bak; Fig. 1B) and critical for GRK2 binding to G-protein ␤␥ dimers (28,29).…”
Section: Fig 1 Domain Organization Of Plc Isozymes and Secondary Stmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments were performed at five magnetic fields of 9.4, 11.7, 14.1, 16.4, and 18.8 Tesla, and used standard pulse sequences (e.g. 33). The NOEs were determined using a flip-back measurement scheme 34 for water suppression, the recycling delay was 4-5 s (see Supporting Table 1 for complete list of relaxation delays).…”
Section: Sample Preparation and Nmr Measurementsmentioning
confidence: 99%
“…For these reasons, we initially analyzed a relatively large construct of the mDvl1 DEP domain, mDvl1(390-498), to ensure that all of the residues of the domain were present in a single construct. After completing the backbone assignments of this construct, heteronuclear 15 N-1 H nuclear Overhauser effects (NOEs) were measured using standard methods 30 . The results indicated that residues 402-495 are well folded and that the Nterminal 10 amino acids is unstructured.…”
Section: Boundaries Of the Dep Domain Of Mdvl1mentioning
confidence: 99%